# algebra

posted by .

How would you solve the systemof equations using the substitution method:

2x-9y=2
4x+18y=12

• algebra -

Take the first equation and solve for x:
2x-9y=2
x=(2+9y)/2
Substitute this value of x into the second equation and solve for y.
Substitute the solution for y into the first equation to find the solution of x.
BACK SUBSTITUTE x and y into both equations to make sure the answer is correct.

• algebra -

how would you solve this prblem n+37 if n is 16

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### Algebra

Systems of equations can be solved by graphing or by using substitution or elimination. What are the pros and cons of each method?
3. ### algebra

o Systems of equations can be solved by graphing or by using substitution or elimination. What are the pros and cons of each method?

5. ### Algebra (Intermediate)

5. Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this. 9x + 6y = 60 -27x Ð 18y = -180 Here's where I am at now: 9x(3) + 6y(3) = 60 27x +18y + 60 27 x + …
6. ### AlgebraII-Reiny could you please check-I'm stuck

Sikve the following by using substitution method x=3y -5 6x-18y = -30 I got this far and I'm stuck 6(3y-5) - 18y = -30 18y - 30 - 18y = -30 -30 = -30 So this doesn't make sense anymore
7. ### Math

How do you solve this by substitution? x=6y+2 3x-18y=4 This is the answer I get: 3(6y+2)-18y=4 18y+6-18y=4 18y+1818y+6-18y+18y=4 36y=10 36 36 Y=5/18 3x-18(5/18) =4 3x-5+5= 4+5 3x= 9 3 3 X=3 (3, 5/18)
8. ### Algebra 1

solve the system of equations using the substitution method. 8x-9=y, y-8x=-4
9. ### algebra

solve the system of equations using the substitution method 8x - 9 = y, y - 8x = 4
10. ### algebra

solve the system of equations using the substitution method 8x - 9 = y y - 8x = -4

More Similar Questions